Sacral Rheumatoid Nodule: An Unusual Indication for Coccygectomy - Zachary R. Porter; Juan C. Mejia-Munne; Bryan M. Krueger; Jennifer A. Kosty; Laura B. Ngwenya (Case Reports in Surgery)
Here, we present a case report of a woman who presented with a large sacral rheumatoid nodule. This patient failed conservative treatment and presented in search of a surgical solution. We successfully removed her rheumatoid nodule using a surgical approach typically reserved for traumatic coccydynia. We show how coccygectomy, although a rare surgical procedure, was effective in treatment of a large rheumatoid nodule.